« Petits meurtres entre amis ». Approche psychosomatique et psychodynamique du harcèlement moral au travail - Marie Grenier-Pezé (Perspectives Interdisciplinaires sur le Travail et la Santé)
The presence of moral harassment in the media questions its own social and psychopathological legitimacy. To understand the formidable toxicity of the harassment situation, identity issues related to the work situation need to be investigated. This new syndrome must be re-situated within the broader framework of the positive and negative effects of work organization on mental and physical health. The individual defence mechanisms and collective strategies that subjects mobilize to cope at work can either strengthen or dismantle a work collective, thus resulting in the creation of a scapegoat. Internalizing the company’s organizational values allows banalization of the harm imposed on others, and its systematization through bodily discipline techniques. Meeting with the network (the company medical officer, the government medical inspector, the general practitioner, the workplace psychologist) is not just a medical and administrative strategy. This networking also puts a symbolic end to the harassed person’s isolation and an end to the evolving psychosomatic symptoms.